2021
DOI: 10.1002/prot.26057
|View full text |Cite
|
Sign up to set email alerts
|

β‐sheet breakers with consecutive phenylalanines: Insights into mechanism of dissolution of β‐amyloid fibrils

Abstract: β‐sheet breakers (BSB) constitute a class of peptide inhibitors of amyloidogenesis, a process which is a hallmark of many diseases called amyloidoses, including Alzheimer's disease (AD); however, the molecular details of their action are still not fully understood. Here we describe the results of the computational investigation of the three BSBs, iaβ6 (LPFFFD), iaβ5 (LPFFD), and iaβ6_Gly (LPFGFD), in complex with the fibril model of Aβ42 and propose the kinetically probable mechanism of their action. The mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 62 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…Another question to address in future studies is to elucidate the critical component in the NCAM-PrP peptide sequence that exhibits this strong amyloid inhibitory effect in several amyloidogenic systems in solution, in membrane-mimicking environments, and in cells. It has been proposed that an important amyloid inhibiting interaction originates from the “FF”-motif ( Mason and Buell 2019 ; Jarmuła et al., 2021 ), both in the Aβ amino acid sequence and of another modulator of Aβ fibrillization, namely LL-37 ( De Lorenzi et al, 2017 ). Interestingly, an “FF”-motif is also present in the NCAM-PrP construct peptide, in the signal NCAM 1-19 sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Another question to address in future studies is to elucidate the critical component in the NCAM-PrP peptide sequence that exhibits this strong amyloid inhibitory effect in several amyloidogenic systems in solution, in membrane-mimicking environments, and in cells. It has been proposed that an important amyloid inhibiting interaction originates from the “FF”-motif ( Mason and Buell 2019 ; Jarmuła et al., 2021 ), both in the Aβ amino acid sequence and of another modulator of Aβ fibrillization, namely LL-37 ( De Lorenzi et al, 2017 ). Interestingly, an “FF”-motif is also present in the NCAM-PrP construct peptide, in the signal NCAM 1-19 sequence.…”
Section: Discussionmentioning
confidence: 99%
“…In the study carried out by Shuaib et al 81 they showed that the Phe 20 has important share in binding free energy to modied iab5 peptide PPFFE. On similar line Jarmuła et al 61 showed that addition of Phe residues into BSB peptide (LPFFFD) and docked around Phe 20 in the CHC region of Ab42 brils help to improve the destabilization potential of peptide. The importance of Phe 19 and Phe 20 was shown by Dutta et al 84 through mutation studies.…”
Section: Discussionmentioning
confidence: 84%
“…[55][56][57][58] Abeta being polymorphic in nature each of the bril structure have its own importance and which have been highlighted in the recent experimental and computational studies. [59][60][61][62][63] Also, studies by Cheon M et al 62 & Kahler A et al 63 suggest formation of U-shaped brillar structure from potent on-pathway intermediates of the Ab17-42 pentamer and hexamer oligomers (paranuclei). The U-shaped model (2BEG) has been part of most of the previously reported molecular simulation studies.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Baicalein displays π–π interactions with the CHC region residue Phe19(A). 43 Baicalein displays hydrophobic contacts with Phe19(A), Phe20(A), Asp23(A), Val24(A), Asn27(A) and Gly29(A) of Aβ 42 protofibrils (Fig. 2(b)).…”
Section: Resultsmentioning
confidence: 99%